What roles do governments play vis-à-vis niche actors? A typology illustrated with transition dynamics in the Dutch agri-food system - Hens Runhaar; Sophie van Doorm; Laura Bello Cartagena; Sabine de Graaff; Charlotte Offringa; Laura van Oers; Nataliia Pustilnik; Evelien Remorie; Willem Lageweg; Rob Raven (Environmental Science & Policy, 2025)

Household innovation and agency in sustainability transitions - Rob Raven; Ruth Lane; Jo Lindsay; David Reynolds; Annica Kronsell (Environmental Innovation and Societal Transitions, 2025)

Governing University Living Labs for sustainability transformations: insights from 18 international case studies - Paris Hadfield; Darren Sharp; Jonas Pigeon; Rob Raven (Sustainability Science, 2025)
In recent years, scholarly debate has grown around a perceived gap between societal impact rhetoric and the support structures for interdisciplinary and applied research, education, and innovation in universities. University Living Labs (UniLLs) provide a window into this relationship as they transcend disciplinary boundaries and linear modes of engagement to enable real-world experimentation and learning in response to societal challenges such as sustainable development. However, few studies examine the institutional contexts in which UniLLs operate, thus limiting our understanding of universities’ capacity for sustainability experimentation. This study examines how the institutional structures, cultures, and practices of universities enable or constrain the governance of sustainability-oriented UniLLs. Our study is grounded in the practical work of organising and conducting UniLLs, drawing on interviews with 39 academics and practitioners involved in UniLLs at 18 universities in Australia, Brazil, Canada, Germany, France, The Netherlands, Singapore, the UK, and the USA. Our research findings demonstrate that (1) UniLLs are enabled by the institutionalisation of sustainable development agendas, and the relational and discursive work of key university staff. (2) UniLLs are often limited in scope and longevity by a project logic and work against entrenched academic and operational organising structures and corporate logics. (3) Some UniLLs overcome these barriers by leveraging institutional power and mobilising resources to embed UniLL governance in university-wide structures. We present practical enabling processes for institutionalising UniLLs in universities demonstrated by the cases and reflect on the university governance paradigm for advancing a transformative impact agenda.

Framing of innovation in urban Australian municipal climate policy - Grace Rodgerson; Megan Farrelly; Rob Raven; Darren Sharp (Environmental Science & Policy, 2025)

Behaviours and practices in socio-technical systems and sustainability transitions: editorial to the virtual special issue - Paul Upham; Stefan Kaufman; Paula Maria Bögel; Rob Raven (Journal of Cleaner Production, 2025)

Place-based and sectoral patterns in urban experimentation: Implications for deep transitions research - Wikke Novalia; Megan Farrelly; Rob Raven (Environmental Innovation and Societal Transitions, 2024)

Household niche experimentation in sustainability transitions and everyday life: A novel framework with evidence from low-waste living in Melbourne - Rob Raven; Jo Lindsay; Ruth Lane; David Reynolds (Environmental Innovation and Societal Transitions, 2024)

Role of local governments and households in low-waste city transitions - Ruth Lane; Annica Kronsell; David Reynolds; Rob Raven; Jo Lindsay (Environmental Innovation and Societal Transitions, 2024)

Decarbonising industry supply chains: Incumbent-oriented transition intermediation for industry energy transition - Alexander Nordt; Rob Raven; Shirin Malekpour; Darren Sharp (Environmental Innovation and Societal Transitions, 2024)

Actors, agency, and institutional contexts: Transition intermediation for low-carbon mobility transition - Alexander Nordt; Rob Raven; Shirin Malekpour; Darren Sharp (Environmental Science & Policy, 2024)

Bottom‐up dynamics in circular innovation systems: The perspective of circular start‐ups - Marvin Henry; Julian Kirchherr; Rob Raven; Marko Hekkert (Journal of Industrial Ecology, 2024)
The concept of circular economy (CE) is proposed to lead humanity toward a sustainable future. Public authorities increasingly build on CE narratives. The progress of private sector actors is key to enable more circular resource flows. Still, the world falls far short from becoming circular and large‐scale implementation of CE in actual problem–solution spaces is scarce. This study sheds light into the external strategies of circular start‐ups (CSUs) in building an adequate socio‐institutional embedding for circular business models (CBMs) and puts the findings in the context of CE and sustainability transformations research. CSUs are a distinct group of CE‐oriented actors that build and implement CBMs wholistically and from scratch. Thereby, they can directly and indirectly contribute to the creation of circular innovation systems. This study defines the common CE mission of CSUs, sets it in context of respective socio‐political CE missions, and scrutinizes the roles that CSUs adopt to drive systemic CE implementation. We observe that CSUs’ strategic interventions go further than only novelty creation. This article proposes and elaborates on four roles that CSUs adopt: conveners , reinforcers , pioneers , and champions . The roles differ according to the CSU business models, stakeholders, the institutional elements that are addressed, as well as the directionalities that CSUs set. The findings are discussed considering the governance, policies, and strategic management of various directionalities in which CE innovation develops. It sheds light on inadequacies and limitations for bottom‐up CE innovation in existing norms and cognition, policy, and network governance.

Pluralising place frames in urban transition management: Net-zero transitions at precinct scale - Darren Sharp; Rob Raven; Megan Farrelly (Environmental Innovation and Societal Transitions, 2024)

Mission-Oriented Innovation Districts: Towards challenge-led, place-based urban innovation - Sebastian Fastenrath; Sam Tavassoli; Darren Sharp; Rob Raven; Lars Coenen; Bruce Wilson; Daan Schraven (Journal of Cleaner Production, 2023)

Transformative potential in sustainable development goals engagement: Experience from local governance in Australia - Dianty Ningrum; Rob Raven; Shirin Malekpour; Enayat A. Moallemi; Brett A. Bryan (Global Environmental Change, 2023)

Flood event attribution and damage estimation using national‐scale grid‐based modelling: Winter 2013/2014 in Great Britain - Alison L. Kay; Naomi Booth; Rob Lamb; Emma Raven; Nathalie Schaller; Sarah Sparrow (International Journal of Climatology, 2018)
A sequence of major flood events in Britain over the last two decades has prompted questions about the influence of anthropogenic greenhouse gas emissions on flood risk. Such questions are difficult to answer definitively, as a range of other factors are involved, but modelling techniques allow an assessment of how much the chance of occurrence of an event could have been altered by emissions. Here the floods of winter 2013/2014 in Great Britain are assessed by combining ensembles of climate model data with a national‐scale hydrological model and, for one severely impacted river basin (the Thames), a detailed analysis of flood inundation and the increased number of residential properties placed at risk. One climate model ensemble represents the range of possible weather under the current climate, while 11 alternative ensembles represent the weather as it could have been had past emissions not occurred. The pooled ensemble results show that emissions are likely to have increased the chance of occurrence of these floods across much of the country, with a stronger influence on longer duration peaks (~10 days or more) than for shorter durations (consistent with observations). However, there is substantial variation in results between alternative ensembles, with some suggesting likely decreases in the chance of flood occurrence, at least in some regions of the country. The influence on flows and property flooding varies spatially, due to both spatial variation in the influence on precipitation and variation in physical properties that affect the transformation of precipitation to river flow and flood impacts, including flood defences. This complexity highlights the importance of using hydrological modelling to attribute hydrological impacts from meteorological changes. Changes in snow occurrence in a warming climate are also shown to be important, with effects varying spatially.

Unpacking sustainabilities in diverse transition contexts: solar photovoltaic and urban mobility experiments in India and Thailand - Rob Raven; Bipashyee Ghosh; Anna Wieczorek; Andy Stirling; Duke Ghosh; Suyash Jolly; Eakanut Karjangtimapron; Sidtinat Prabudhanitisarn; Joyashree Roy; Somporn Sangawongse; Frans Sengers (Sustainability Science, 2017)

Upscaling of business model experiments in off-grid PV solar energy in India - Suyash Jolly; Rob Raven; Henny Romijn (Sustainability Science, 2012)

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)